Model kepemimpinan Musa dan relevansinya bagi kepemimpinan Kristen masa kini - Rapi Gultom (Sekolah Tinggi Alkitab Penyebaran Injil (STAPIN) Majalengka, 2026)
In the context of a church facing the challenges of social change, a crisis of integrity, digital dynamics, and the need for profound spiritual development, the figure of Moses offers leadership principles that remain significant and applicable. This study aims to analyze Moses' leadership model in the Old Testament and evaluate its relevance for contemporary Christian leadership. This study employed a library research method with a theological-biblical approach and conceptual analysis through adaptive leadership theory to assess Moses' leadership pattern and its implications for the modern church. The results indicate that Moses' leadership reflects five main aspects: God-centered leadership, character-based leadership, adaptive leadership, relational leadership, and transformative leadership. These five aspects have proven relevant to addressing various challenges of contemporary Christian leadership, including the moral crisis, the need for spiritual identity formation, the demands of multigenerational communication, and navigating issues in the digital age. This analysis confirms that Moses' leadership model is not merely historical but also serves as an applicable framework that can enrich and strengthen Christian leadership practice amidst changing times.